Borrowing Risk and the Tequila Effect - Agenor, Pierre-Richard (IMF Working Papers; Working Paper, 1997)
This paper models the Tequila effect (triggered by the collapse of the Mexican peso in December 1994) as a temporary increase in the risk premium faced by domestic private borrowers on world capital markets. The effects of this shock are studied in an intertemporal optimizing framework where firms' demand for working capital is financed by bank credit. Under the assumption that the perceived duration of the shock is sufficiently long, the model is capable of reproducing some of the main features of Argentina's economic downturn in the aftermath of the collapse of the Mexican peso: the rise in domestic interest rates, the reduction in net private capital inflows and the drop in official reserves, the reduction in bank deposits and credit supply, the fall in private consumption, the contraction in output, and the increase in unemployment.